Effects of barley crop residues on weed management and grain yield of transplant Aman rice (Progressive Agriculture, 2020)
The experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University during the period from July to December 2017 to evaluate the effect of barley crop residues on weed management and yield of transplant aman rice. The experiment consisted of three time of crop residue application viz. one week before transplanting, at the time of transplanting, at one week after transplanting and five doses of barley crop residues such as no crop residues, barley crop residues @ 0.5 t ha-1, barley crop residues @ 1.0 t ha-1, barley crop residues @ 1.5 t ha-1, and barley crop residues @ 2.0 t ha-1. The experiment was laid out in a split plot design with three replications. Weed population and weed dry weight were significantly affected by the dose and time of barley crop residues application. The minimum weed growth was noticed with the application of barley crop residues @ 2.0 t ha-1 at one week after transplanting and the maximum one was observed in no crop residues treatment at one week before transplanting. The highest values of percent weed inhibition was found with the application of barley crop residues @ 2.0 t ha-1 which were 48.13%, 41.39%, 39.71%, 39.88% and 38.73% for panikachu (Monochoria vaginalis), shama (Echinochloa crusgalli), chesra (Scirpus juncoides), amrul (Oxalis corniculata) and sabujnakful (Cyperus difformis), respectively. Rice grain yield and the yield contributing characters produced by the application of crop residues at one week before transplanting was the highest among different times of application and the highest reduction of rice grain yield was obtained in no crop residue treatment. The highest number of effective tillers hill-1, number of grains panicle-1, 1000-grain weight, rice grain and straw yields were observed when barley crop residues were applied @ 2.0 t ha-1 at one week before transplanting.  Results of this study indicate that application of barley crop residues @ 2 t ha-1 at one week before transplanting showed the maximum suppression of weed growth. Therefore, barley crop residues might be used as an alternative tool for weed management in transplant aman rice.Progressive Agriculture 31 (2): 119-129, 2020